2018
DOI: 10.1002/adv.21939
|View full text |Cite
|
Sign up to set email alerts
|

Manifestation of accelerator type and vulcanization system on the properties of silica‐reinforced SBR/devulcanize SBR blend vulcanizates

Abstract: Mechanochemically devulcanized styrene-butadiene rubber, prepared by bis [3-(triethoxysilyl)propyl]-tetrasulfide, was blended with fresh styrene-butadiene rubber. The ultimate properties of the blend vulcanizate depend on a three-dimensional network structure formed during vulcanization which relies mainly on the accelerator and the vulcanizing system used during compounding. The effect of monosulfide, disulfide, and poly sulfide cross-links, which primarily gets controlled by different accelerators such as N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…The greater the stiffness of the vulcanizate, the greater the SE 100 and SE 300 modules. Thus, SE 100 and SE 300 depend on the type of filler used, crosslink density of the vulcanizates and the structure of crosslinks 13 . All tested vulcanizates were filled with 30 phr of carbon black, therefore the influence of the filler on these parameters can be neglected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The greater the stiffness of the vulcanizate, the greater the SE 100 and SE 300 modules. Thus, SE 100 and SE 300 depend on the type of filler used, crosslink density of the vulcanizates and the structure of crosslinks 13 . All tested vulcanizates were filled with 30 phr of carbon black, therefore the influence of the filler on these parameters can be neglected.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the type of accelerator used is no less important in terms of cure characteristics and properties of elastomer composites 13–16 . Moreover, Azar et al 17 postulated a strong dependence between the type of accelerator and both the network structure and crosslink density of the vulcanizates.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the curing system composition, i.e., the sulfur/accelerator ratio and the type of accelerator used, has been extensively studied for various rubbers [7][8][9][10][11][12]. For example, Formela et al [10] applied different accelerators to vulcanize reclaimed rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh et al [12] confirmed that the sulfur/accelerator ratio and the type of accelerator significantly affected the cure characteristics, vulcanization efficiency and thus mechanical performance of rubber blends composed of raw styrene-butadiene rubber (SBR) and mechanochemically devulcanized SBR. The CV, semi-EV and EV curing systems based on thiurams, thiazoles and sulfenamide accelerators were applied.…”
Section: Introductionmentioning
confidence: 99%
“…), and delayed action accelerators (sulfenamide, etc.) in the vulcanization process of rubbers. The kinetics order of the vulcanization induction period ( t 10 ) of several accelerators in SBR’s vulcanization process is CBS > TBBS > MBT > TMTD, while that of the vulcanization time ( t 90 ) is TMTD > CBS > TBBS > MBT (CBS = N -cyclohexyl-benzothiazyl-sulfenamide, TBBS = N - tert -butyl-2-benzothiazyl-sulfonamide, MBT = 2-mercaptobenzothiazol, TMTD = tetramethylthiuram disulfide). At the molecular level of the vulcanization process, in 2001, Nieuwenhuizen et al introduced the model-compound vulcanization (MCV) method to simplify the rubber molecular chain and used the quantum chemical method to investigate a part of the sulfur vulcanization mechanism of natural rubber activated by the ZDMC vulcanization accelerator . In 2006, Steudel et al discovered that TMTD and ZnO could produce ZDMC in the vulcanization process of natural rubber based on theoretical results, which could speed up the cross-linking process .…”
Section: Introductionmentioning
confidence: 99%